Answer:
The initial height of the base ball based on the equation for the height of the base ball,
is 3 ft
Explanation:
For clarity, if we put the equation of the height of the base ball as
![h = -16t^2 + 32t + 3](https://img.qammunity.org/2021/formulas/mathematics/high-school/y6onqedr1fgropkdgoibsbix1khbdmnglc.png)
Then the initial height of the base ball will be at the point t = 0
That is
or
h = 3 ft
The initial height of the base ball based on the equation for the height of the base ball,
is then = 3 ft.